Effects of medicinal herbs "Plantago asiatica", "Houttuynia cordata" and "Mentha haplocalyx" on non-specific immune responses of cobia (Rachycentron canadum). (November 2016) - Wu, Yu-Sheng; Chen, Yin-Yu; Ueng, Pien-Sheng; Nan, Fan-Hua
Abstract: This study investigated the effects of orally administered Plantago asiatica, Houttuynia cordata, and Mentha haplocalyx on the growth and nonspecific immune responses of cobia ( Rachycentron canadum ). The nonspecific immune parameters assessed were weight gain, feed conversion ratio, superoxide anion (O2 − ) production, superoxide dismutase (SOD) activity, phagocytic rate, phagocytic index, lysozyme activity, serum albumin and globulin, and albumin:globulin (A/G) ratio. The growth experiment indicated that 6-week dietary treatments did not significantly affect on the growth of cobia. Nonspecific immune responses showed that O2 − production, SOD and lysozyme activity, and phagocytosis were significantly increased after the oral administration of P. asiatica and H. cordata, and the serum albumin:globulin ratio (A/G) gradually decreased. In this study, treatment of the Mentha haplocalyx on the cobia didn't present with the inducing of the phagocytosis ability compared with the treatment of P. asiatica and H. cordata. We suggest that oral administration of the 10 g/kg or 20 g/kg of the P. asiatica and H. cordata is exactly inducing the phagocytosis, ROS production, lysozyme activity and SOD production in the cobia. Highlights: Using of medicinal herbs " P. asiatica ", " H. cordata " and " M. haplocalyx did not inhibit the growth of cobia. 10 and 20 g/kg of P. asiatica and H. cordata are enhancing the ROS, phagocytosis and Lysozyme activity. Oral administration of P. asiatica and H. cordata, and the serum albumin: globulin ratio (A/G) gradually decreased.